Telemedicine in neurology: advances and possibilities - Aquino, Emanuelle Roberta da Silva; Suffert, Soraya Camargo Ito (Arquivos de Neuro-Psiquiatria, 2022)
Background: Telemedicine develops from technology that offers opportunities for knowledge transfer and information sharing and allows the provision of health services at a distance. Objective: To evaluate the number of publications on teleneurology in the last two decades in PubMed and the available evidence on the use of this technology in neurological clinical conditions. Methods: A quantitative assessment of publications related to telemedicine and neurology in the last two decades. A search was performed on the PubMed database for the descriptors ("Telemedicine"[Mesh]) AND "Neurology"[Mesh]). A review of the articles retrieved on the topic was carried out to evaluate the innovation processes used and applications in various clinical conditions involving teleneurology. Results: The search performed on March 14th 2022 resulted in 229 publications involving the topic of telemedicine and neurology between 1999 and 2022. Since 2000, there has been an increase in publications related to this topic, with a peak of 71 articles published in 2020, the year in which the World Health Organization defined the COVID-19 pandemic status. Conclusion:  In the last two decades, teleneurology has been developing through the expansion of technological resources and the COVID-19 pandemic intensified this process. Different modalities of teleneurology are studied in several neurology subfields and include teleconsultation (between healthcare professionals or between healthcare professionals and patients), telerehabilitation, telemonitoring and tele-education. The advances achieved by teleneurology in this period encouraged technological innovations and health processes that developed opportunities to improve the care provided in a mechanism of constant evolution.
Keywords: Telemedicine; Neurology; Remote Consultation; COVID-19; Delivery of health care